2018
DOI: 10.26417/ejnm.v1i1.p59-66
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Environmental Factors Associated with Pulmonary Tuberculosis in Prisoners in Northeastern Brazil

Abstract: This study aimed to assess clinical and environmental factors associated with pulmonary tuberculosis in prisoners. We carried out a documentary, retrospective, epidemiological study of records of tuberculosis cases in a prison hospital in Northeastern Brazil. The sample consisted of data from medical records of prisoners diagnosed with TB from January 2015 to January 2016. Information such as age, race, marital status, education level, weight, height, harmful habits, and clinical data on mucous membrane, cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The pooled results showed that prisoners coughing ≥2 weeks were 0.08 times more likely to be infected with TB than their counterparts. Similarly, two studies 67,68 that looked at the length of coughing indicated that patients who coughed for 2 weeks or more had a higher risk of contracting the illness than patients who coughed for less time or did not cough. This is due to the fact that a TB patient's infectiousness is directly correlated with the quantity of tubercle bacilli that they discharge into the air.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled results showed that prisoners coughing ≥2 weeks were 0.08 times more likely to be infected with TB than their counterparts. Similarly, two studies 67,68 that looked at the length of coughing indicated that patients who coughed for 2 weeks or more had a higher risk of contracting the illness than patients who coughed for less time or did not cough. This is due to the fact that a TB patient's infectiousness is directly correlated with the quantity of tubercle bacilli that they discharge into the air.…”
Section: Discussionmentioning
confidence: 99%